Short-term efficacy and safety of lasmiditan, a novel 5-HT1F receptor agonist, for the acute treatment of migraine: a systematic review and meta-analysis - Hou, Min; Xing, Haiyan; Li, Chen; Wang, Xianfeng; Deng, Dongmei; Li, Juan; Zhang, Pan; Chen, Jianhong (Journal of headache and pain, 2020)
Background Migraine has been recognized as one of common diseases in the world whose current treatment options are not ideal. Lasmiditan, an oral 5-hydroxytryptamine (HT) 1F receptor agonist, appears more promising for the acute treatment of migraine because of considerably better effect profiles with no severe adverse events (AEs). This review aimed to systematically evaluate the efficacy and safety of lasmiditan from the results of randomized controlled trials (RCTs). Methods PubMed, Cochrane Library, Embase were searched on lasmiditan for the acute treatment of migraine from inception of the databases to Feb 1, 2020. Pain free and pain relief, global impression (very much/much better), and no/mild disability at 2 h in efficacy; total treatment-emergent adverse events (TEAEs), dizziness, nausea, fatigue, paraesthesia and somnolence in safety were extracted from the included studies. A systematic review and meta-analysis was performed using Review Manager Software version 5.3 (RevMan 5.3). Results Four RCTs with a total of 4960 subjects met our inclusion criteria. The overall effect estimate showed that lasmiditan was significantly superior to placebo in terms of pain free (RR 1.71, 95% CI 1.55–1.87), pain relief (RR 1.40, 95% CI 1.33–1.47), global impression (very much/much better) (RR 1.55, 95% CI 1.44–1.67), and no/mild disability (RR 1.15, 95% CI 1.10–1.20) at 2 h. For the safety, significant number of patients experienced TEAEs with lasmiditan than with placebo (RR 2.77, 95% CI 2.53–3.03), most TEAEs were central nervous system (CNS)-related and included dizziness (RR 5.81, 95% CI 4.72–7.14), nausea (RR 2.58, 95% CI 1.87–3.57), fatigue (RR 5.38, 95% CI 3.78–7.66), paraesthesia (RR 4.48, 95% CI 3.33–6.02), and somnolence (RR 2.82, 95% CI 2.18–3.66). Conclusions This meta-analysis suggests that lasmiditan is effective for the acute treatment of migraine with a higher incidence of CNS-related adverse reactions compared with placebo. Long-term, open-label, multi-dose trials are required to verify the current findings.